RS-485 Bus Design of a Missile Simulation Training System - Xinjie Ji Xinjie Ji; GuozhouWang GuozhouWang; FangLiu FangLiu (Universitas Ahmad Dahlan, 2013)
In a missile simulation training system with one-master and multi-slaves distributed system structure, a universal controller is necessary due to the system composed with several controllers. In this research, the designed controllers communicate with each other and upper control computer through RS-485 field bus. RS-485 bus including interface circuits, transmission protocol, Cyclic Redundancy Check (CRC) method and upper control test software is designed and proposed. The universal controller adopting the designed RS-485 interface circuits is connected through twisted-pair and makes the simulation system, then the controller is tested in line. The results show that the RS-485 bus communicates effectively using the protocol and CRC method, data transmission rates reaches 115.2 kbps, and has a good stability.